2-Vinyloxycarbonyloxymethyl antraquinone as a new unsaturated photoinitiator for UV-cured acrylic pressure-sensitive adhesives - Czech, Z. (Polimery, 2022)
Modern UV-curing technology requires efficient and very effective photoinitiators. The best technological solution is the use of unsaturated photoinitiators incorporated into the polymer chain during the synthesis of a pressure-sensitive adhesive (PSA) and being active in its UV-curing. In this work the unsaturated photoinitiator based on antraquinone [VCMA, formula (I)], in amounts from 0.1 to 2.0 wt. %, was used in the syntheses of photoreactive PSA made of 2-ethylhexylacrylate, methyl acrylate and acrylic acid. The obtained photoreactive polyacrylic adhesives, coated onto polyester films, were cured by UV lamp. Adhesion and cohesion of PSA were determined, dependently on photoinitiator concentration and UV curing time. It was found that high values of adhesion and cohesion were reached when photoinitiator concentration was about 0.5 wt. % and curing time about 2.5-3 min. Photoreactive polyacrylic adhesives, described and characterized in the article, synthesized with use of 2-vinyloxycarbonyloxymethyl antraquinone as photoinitiator, can be used in the wide range of technical and medical pressure-sensitive products.